BALANCED SCORECARD: LEARNING AND GROWTH PERSPECTIVE - Utomo, St. Dwiarso; Machmuddah, Zaky; Setiawanta, Yulita (Univesitas Muhammadiyah Malang, 2019)
The purpose of the research is to find an empirical evidence concerning the implementation of learning and growth perspective of Balanced Scorecard (BSC) in Assalaam Islamic Modern Boarding School Surakarta (AIMBSS) and to find factors supporting and being handicap of implementation of learning and growth perspective of BSC. The research will widen the object scope being able to be approached by BSC. It is a case study research. Qualitative research design is conducted using semi-structured interviews with 12 respondents from different stakeholders. Research findings showed that principally learning and growth perspective of BSC and attributes in strategy map of BSC have been implemented well in some levels of management in AIMBSS. Besides, the research found supporting factors of implementation of learning and growth perspective of BSC in AIMBSS, namely: strong commitment from management to adapt the change and most of employees are ready to adjust themselves with the change. Meanwhile, handicapped factor of implementation of learning and growth perspective of BSC in AIMBSS is resistant from certain employees. It causes the effectivity of system. For future research, it is suggested to add the number of research object so that the generalization of the research findings can be gained.